PMMA Cranioplasty Making by Using Оpen-Source CAD Software, PLA Printers, and Silicone Rubber Molds: Technical Note with Two Illustrative Cases - Malikov, Azad; Secen, Ahmet Eren; Ocal, Ozgur; Divanlioglu, Denizhan (Asian Journal of Neurosurgery, 2022)
In this technical report, we discuss the design and production of polymethyl methacrylate (PMMA) implants, which we successfully applied in two patients using silicone molds, and a retrospective review of these patients at 1- and 6-month intervals. By using open-source computer-assisted design software, three-dimensional printers, and the patient's thin-sliced computed tomography data, we designed and produced the implant template and used it to make silicone rubber mоlds for intraoperative PMMA casting with good results. As a negative of the implant, we created a silicon mold, which can be autoclaved.Two patients underwent PMMA cranioplasty using this method. Both implants were fitted into the defect without manipulation and good aesthetic аppеаrance of all patients was achieved. At follow-up 1 and 6 months after the operation, no complication was noted and the patients tolerated the cranioplasty platе wеll.
Keywords: PMMA cranioplasty; PLA printer; silicone mold